Transformational Leadership: The Role of The Public School Principal in Effective Decision Making - Kurnia, Nia; Nurdin, Diding; Triatna, Cepi; Juliah, Dedeh (International Journal of Educational Management and Innovation, 2026)
Background . The increasingly complex and uncertain education system demands that principals make strategic decisions that not only ensure organizational effectiveness but also drive continuous quality improvement. Although transformational leadership is considered relevant because it emphasizes shared vision, participation, and empowerment, empirical evidence on how these principles are operationalized in the decision-making practices of public elementary school principals remains limited, particularly in the context of novice leadership. This study aims to analyze in depth the decision-making practices of principals with a Guru Penggerak background in two public elementary schools in Sumedang Regency, their impact on school quality improvement, and the challenges and strategies they use to overcome them. Method. Using a qualitative case study design, data were collected through in-depth interviews with two principals and six teachers, and then analyzed thematically with systematic procedures to ensure credibility and consistency of interpretation. Result. The findings indicate that democratic, collaborative, adaptive, reflective, and data-driven decision-making practices reflect the core dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, which contribute to improving school climate, teacher performance, student learning outcomes, and strengthening professional development. Challenges such as limited resources, ethical dilemmas, and policy constraints are addressed through inclusive communication, ethical reasoning, and strategic use of data. Conclusion. This study empirically clarifies the concrete mechanisms that link principals' decision-making practices to transformational leadership theory in a VUCA context, while also confirming its contribution as a conceptual and practical framework for strengthening school leadership capacity.